1989
DOI: 10.1002/mus.880120412
|View full text |Cite
|
Sign up to set email alerts
|

Delayed‐onset muscle damage and lipid peroxidation in man after a downhill run

Abstract: Lipid peroxidation initiated by free radical reactions is associated with tissue necrosis in a variety of conditions. We have measured serum lipid peroxide concentrations (as total thiobarbituric acid-reactive substances, TBARS) and creatine kinase (CK), lactate dehydrogenase (LDH), and aspartate aminotransferase (AST) activities and subjective muscle soreness in 16 men before and after a 45-minute downhill treadmill run. TBARS concentrations and enzyme activities were increased after exercise, with peak value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
1
9

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(96 citation statements)
references
References 23 publications
5
81
1
9
Order By: Relevance
“…al. 16 , which demonstrates that lipoperoxydes have their concentration increased in the plasma up to six hours after intense exercise.…”
Section: Discussionmentioning
confidence: 87%
“…al. 16 , which demonstrates that lipoperoxydes have their concentration increased in the plasma up to six hours after intense exercise.…”
Section: Discussionmentioning
confidence: 87%
“…For standardization of exercise, age and gender matched athletes were chosen for the study. Some parameters of oxidative stress may not change after exercise, and may reach their maximum levels only hours or even days after the end of exercise [21,30]. In several studies, investigators have failed to observe any signs of exercise-induced oxidative stress immediately after exercise [14,22,25].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that, two days of intense exercise increased the plasma total antioxidant capacity in elite skiers [34]. In many studies, it has been shown that oxidative stress parameters did not change [2,12] or increased [21,30] and even decreased [23] after exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Blood LDL concentrations have been found to peak by 6h post exercise and return to resting levels by 48h post exercise (Maughan et al, 1989), while CK concentrations are markedly elevated for 12-24 h after the exercise bout (Semple et al, 2007).…”
Section: Creatine Phosphokinase (Cpk) and Lactate Dehydrogenase (Ldh)mentioning
confidence: 99%